Pilomatrical Tumor of Low Malignant Potential: A Tumor Between Pilomatricoma and Pilomatrical Carcinoma. (4th February 2021) - Collina, Guido; Filosa, Alessandra; Requena, Luis
Abstract: We report a case of pilomatrical tumor showing intermediate histological features between pilomatricoma and pilomatrical carcinoma. The lesion recurred twice with the same histological features. Similar cases were was probably called aggressive or proliferating pilomatixoma; we think that the term pilomatrical tumor of low malignant potential is more suitable for this lesions. Excision with wide free margins and follow-up are recommended.